Gestational Choriocarcinoma in a Jehovah's Witness: A Case Report - Onyinye Onyeka Okonkwo; George Uchenna Eleje; John EN Okonkwo (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2015)
Introduction: Due  to  strong  religious  faith  and  beliefs  against  blood  transfusions,  Jehovah's Witness  patients  often  pose  tight  spot  for  obstetrician-gynecologists. Myelosuppressive  effects  of chemotherapy in gynecology-oncology settings are additional source of worry. Case Presentation: A 25-year-old P0+1 Nigerian woman presented with subcostal pains, dyspnea and cough productive of bloody sputum of one month duration. There was no vaginal bleeding. She  had  spontaneous  miscarriage  and  evacuation  of  retained  products  of  conception  twice  at another health facility with histology confirming choriocarcinoma. She was anemic and had a Durable- Power-of-Attorney  card  forbidding  blood  transfusion.  She  received  Iron  dextran  and  erythropoietin prior to each of three courses of  olychemotherapy. Beta-Human Chorionic Gonadotrophin returned to normal 456 days later and had normal pregnancy sixteen months later. Conclusion: This first reported case of gestational choriocarcinoma in a Jehovah's Witness who survived  without  obstetrics  sequalae  is  illustrative  of  such  managed  in  resource-poor  setting  while maintaining patient autonomy.